Conceptualizing Social Attention in Developmental Research. Issue 4 (29th December 2015) - Salley, Brenda; Colombo, John
Abstract: The term social attention has become widely used during the last decade, appearing within behavioral neuroscience and developmental neurocognitive literatures to characterize a variety of activities and cognitive processes that emerge in the presence of conspecifics. We provide here an overview of the current status of social attention as a construct, as reflected in its appearance in research studies, and we offer a framework for characterizing the extant literature based on the functions of social attention processes: as behavior for social communication, as motivation to engage in social communication, and as a form of basic visual attention in the context of other social agents. We then provide two overarching questions to guide future research efforts directed toward establishing the utility of social attention as an independent and/or unified construct. We then consider implications and recommendations for future research efforts.